The Impact of Psychiatric Comorbidity on Quality of Life in Patients Undergoing Herniated Disc Surgery - Stengler, K.; Zieger, M.; Luppa, M.; Meisel, H.J.; Günther, L.; Meixensberger, J.; Toussaint, R.; Angermeyer, M.C.; König, H.-H.; Riedel-Heller, S.G. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Recent studies examined the role of psychiatric comorbidity in the process of rehabilitation in patients undergoing herniated disc surgery. These patients suffer from physical and psychosocial complaints or symptoms, which impact their everyday life negatively and the success of rehabilitation potentially. The objectives of this study are (1) to examine the quality of life (QoL) in disc surgery patients and to compare the findings with reference data from the general German population, and (2) to investigate the impact of psychiatric comorbidity on QoL of patients undergoing herniated disc surgery.Methods This study consists of 305 patients aged between 18 and 55 years who took part in face-to-face interviews during their hospital stay. Psychiatric comorbidity was assessed with the Composite International Diagnostic Interview (CIDI-DIA-X). By means of the 36-Item Short-Form Health Survey (SF-36), QoL was assessed in patients undergoing herniated disc surgery with and without psychiatric comorbidity. These findings were compared with the QoL of a representative sample of the general German population.Results Compared with the general population, QoL in patients with herniated disc surgery was lower in all domains of the SF-36. Psychiatric comorbidity impacts the QoL in patients with herniated disc surgery in all SF-36 domains except “physical function”. The patients with psychiatric comorbidity showed significantly lower levels of QoL in the domains “bodily pain”, “vitality”, “social function”, “role emotional”, and “mental health”.Conclusions Psychiatric comorbidity has a substantial adverse effect on QoL in patients undergoing disc surgery. Therefore, it will be necessary to diagnose psychiatric comorbidities at an early stage and to include psychosocial interventions in the treatment of herniated disc patients aimed at improving deficits in psychosocial functioning and QoL.
Keywords: quality of Life; disc surgery; psychiatric comorbidity